Guide to construction and use of 6.30 mm (0.25 in) magnetic tape cartridge for data interchange, using IMFM recording at 252 ftpmm (6400 ftpi). Track format and method of recording for data interchange in start/stop mode Part 2, (31st July 1989) - British Standards Institution,
No abstract available